2022
DOI: 10.3389/fneur.2022.1017565
|View full text |Cite|
|
Sign up to set email alerts
|

Cerebral venous thrombosis in Latin America: A critical review of risk factors, clinical and radiological characteristics

Abstract: BackgroundCerebral venous thrombosis (CVT) is a rare disease that frequently occurs in young women of childbearing age, with variable clinical presentation in regions with limited access to diagnostic imaging or specialized neurological care. In the last decade, there has been an increase in the number of studies on CVT in Latin America, which may contribute to a better epidemiological description of the disease in this region and, consequently, its early diagnosis.ObjectivesOur study aims to review the risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Moreover, several studies have shown the transverse sinus (TS) to be the most common CVST location, its occurrence increasing further in multiple-DVS involvement or when both sides are considered (Bezerra et al, 2022;Duman et al, 2017;Ferro et al, 2004). Regarding the etiological causes of CVST, several well-known general risk factors such as oral contraceptive use, pregnancy, infections, malignancy, and hypercoagulable states have been documented (Bezerra et al, 2022;Duman et al, 2017;Ferro et al, 2021Ferro et al, , 2004Jianu et al, 2018;Zhou et al, 2022Zhou et al, , 2023. Furthermore, other structural factors such as intraluminal bands, intraluminal arachnoid granulations, TS stenosis, absent TS, and extraluminal tumors have been discussed as causes of venographic filling defects and venous flow abnormalities, and are probably implicated in the mechanisms of development of diseases affecting the DVSs such as CVST (Altafulla et al, 2020;Guduri et al, 2023;Iwanaga et al, 2020;Strydom et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, several studies have shown the transverse sinus (TS) to be the most common CVST location, its occurrence increasing further in multiple-DVS involvement or when both sides are considered (Bezerra et al, 2022;Duman et al, 2017;Ferro et al, 2004). Regarding the etiological causes of CVST, several well-known general risk factors such as oral contraceptive use, pregnancy, infections, malignancy, and hypercoagulable states have been documented (Bezerra et al, 2022;Duman et al, 2017;Ferro et al, 2021Ferro et al, , 2004Jianu et al, 2018;Zhou et al, 2022Zhou et al, , 2023. Furthermore, other structural factors such as intraluminal bands, intraluminal arachnoid granulations, TS stenosis, absent TS, and extraluminal tumors have been discussed as causes of venographic filling defects and venous flow abnormalities, and are probably implicated in the mechanisms of development of diseases affecting the DVSs such as CVST (Altafulla et al, 2020;Guduri et al, 2023;Iwanaga et al, 2020;Strydom et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, multiple‐DVS involvement can occur. Moreover, several studies have shown the transverse sinus (TS) to be the most common CVST location, its occurrence increasing further in multiple‐DVS involvement or when both sides are considered (Bezerra et al, 2022; Duman et al, 2017; Ferro et al, 2004). Regarding the etiological causes of CVST, several well‐known general risk factors such as oral contraceptive use, pregnancy, infections, malignancy, and hypercoagulable states have been documented (Bezerra et al, 2022; Duman et al, 2017; Ferro et al, 2021, 2004; Jianu et al, 2018; Zhou et al, 2022, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main risk factors of CVST include thrombocytosis (polycythemia), hemodynamic changes (stasis or turbulence of blood flow), vascular endothelial damage, pregnancy, oral contraceptive pills consumption, anticoagulation therapy, lumbar puncture, blood disorders, like myeloproliferative diseases, hereditary thrombophilia, hyperhomocysteinemia, and paroxysmal nocturnal hemoglobinuria (PNH) (5). Different studies have demonstrated an association between intravenous sinus thrombosis and iron deficiency anemia (IDA), and several mechanisms have been proposed to explain this relationship (6,7).…”
Section: Introductionmentioning
confidence: 99%